Pengembangan Dimensi Destination Image Terhadap Keputusan Berkunjung Di Ekowisata Boon Pring Malang - Laila Romadhona Rahma; Rohmad Prio Santoso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The decision to visit tourists is an integrative process that combines information to evaluate two or more alternative options and choose one of them. The aim of the study was to find out how the dimensions of the destination image, which consists of cognitive image of the destination, unique image of the destination, and image of the destination, have an impact on the decision to visit Boon Pring Malang ecotourism. This research uses a quantitative approach with a causal or causal approach. The number of respondents as many as 80 visitors. The results showed that (1) partially the cognitive destination image variable has a positive and significant influence on the decision to visit Boon Pring Malang ecotourism, the supporting factors are tourist images on social media that look attractive (2) unique destination image has a partial effect on the decision to visit ecotourism boon pring Malang, the supporting factors are having various types of bamboo and springs (3) affective destination image has a partial effect on the decision to visit Boon Pring Malang ecotourism, the supporting factors are the influence of the attitude of visitors after visiting feeling happy (4) together (simultaneously) cognitive, unique, affective destination image has a positive and significant impact on decisions about visiting Boon Pring Malang ecotourism.